2008
DOI: 10.2116/analsci.24.763
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bis(amino alcohol)oxalamides and Their Usage for the Preconcentration of Trace Metals by Cloud Point Extraction

Abstract: C2-Symmetric two bis(amino alcohol)oxalamides (diamidediols) were synthesized and fully characterized. A new method was developed and successfully applied for the simultaneous preconcentration of both trace and toxic metals in water, by using C2-symmetric compounds. Under the optimum experimental conditions (i.e. pH = 10.10% w/v octylphenoxy-polyethoxyethanol (Triton X-114)), calibration graphs were linear in the range of 2.5 -25.0 ng mL -1 for Cu and Cd, 5.0 -25.0 ng mL -1 for Co and Ni. The enrichment factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…This method has a very low limit of detection (LOQ), good relative standard deviation (RSD) and was applied to determine trace amounts of Zn 2+ and Cd 2+ ions in various real samples. In a full comparison of the results presented in this paper with those using similar methods reported in literature 1,7,8,13,43,44 (Table 6) revealed that, on key measurements, the proposed method proved comparable or superior to the reported methods.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…This method has a very low limit of detection (LOQ), good relative standard deviation (RSD) and was applied to determine trace amounts of Zn 2+ and Cd 2+ ions in various real samples. In a full comparison of the results presented in this paper with those using similar methods reported in literature 1,7,8,13,43,44 (Table 6) revealed that, on key measurements, the proposed method proved comparable or superior to the reported methods.…”
Section: Resultssupporting
confidence: 54%
“…Several methods have been developed to separate and determine Zn 2+ or Cd 2+ ions. Traditionally, organic solvents [8][9][10][11][12] have been used to extract Zn 2+ or Cd 2+ ions. However, these solvents are often classified as having carcinogenic toxicity and being environmental pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low concentration of these metals in the environmental and biological samples and interfering effects, a preconcentration/separation technique is generally necessary prior to the determination. For this purpose, various analytical procedures have been used, such as adsorption on activated carbon [3,4] co-precipitation [5,6] column extraction [7,8] ion-selective electrode [9,10] liquid-liquid extraction (LLE) [11] and cloud-point extraction (CPE) [12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, It is simple, cheap, highly efficient, fast, and of lower toxicity than those extractions that use organic solvents. This method has been applied for extraction and preconcentration of some metal ions such as Cu, Ni, Co and Zn in water samples [12], Ag, Zn, and Pb in environmental samples [13], Mo in sea water [14], Cd, Pb, Pd and Ag in environmental samples [15], Cr, Pb, Cu, Ni, Bi, and Cd in environmental samples [16], Cd, Cu, Co and Ni in water [17], U, Th, Zr and Hf in aqueous samples [18], Be in water [19], La, Eu and Lu [20], Rh [21] and Yb, Gd, Eu, Sm, Sc, Ho in biological samples [22].…”
Section: Introductionmentioning
confidence: 99%
“…For this kind of method, phase separation due to changing the temperature and/or the addition of a saltingout reagent has been commonly used for the extraction, purification, and preconcentration of metals. [1][2][3][4][5] A micellar solution of anionic surfactants shows phase separation when the solution is cooled below the Krafft point temperature. These are the surfactant-depleted (aqueous phase) and surfactant-rich (surfactant phase) phases.…”
Section: Introductionmentioning
confidence: 99%